2019
DOI: 10.4102/ojvr.v86i1.1755
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal activity of ticks infesting domestic dogs in Bejaia province, Northern Algeria

Abstract: This epidemiological study aimed to determine the species of tick infestation in dogs, their prevalence and dynamic in the Bejaia province, northeastern Algeria. A total of 631 dogs were examined from different localities of the Bejaia province between March 2016 and February 2017. Of the 631 examined dogs, 15% were infested with one or more tick species. A total of 339 adult ticks were collected and identified, including 199 male tick species and 140 female tick species. Our results revealed that most of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In line with our findings, the brown dog tick, R. sanguineus, has been reported to be the most prevalent tick species of dogs in Nigeria (Adetayo et al, 2021;Akande et al, 2018;Kamani et al, 2018;Shitta et al, 2018) and other parts of the world including Algeria (Kebbi et al, 2019) Egypt (Abdullah et al, 2016), Great Britain (Smith et al, 2011), Italy (Maurelli et al, 2018), Indonesia (Hadi et al, 2016) and China (Zhang et al, 2017). The 61.8% prevalence of R. sanguineus we observed in this study is within the prevalence documented by previous researchers on the abundance of R. sanguineus within and outside of Nigeria (Abdullah et al, 2016;Akande et al, 2018;Maurelli et al, 2018;Shitta et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In line with our findings, the brown dog tick, R. sanguineus, has been reported to be the most prevalent tick species of dogs in Nigeria (Adetayo et al, 2021;Akande et al, 2018;Kamani et al, 2018;Shitta et al, 2018) and other parts of the world including Algeria (Kebbi et al, 2019) Egypt (Abdullah et al, 2016), Great Britain (Smith et al, 2011), Italy (Maurelli et al, 2018), Indonesia (Hadi et al, 2016) and China (Zhang et al, 2017). The 61.8% prevalence of R. sanguineus we observed in this study is within the prevalence documented by previous researchers on the abundance of R. sanguineus within and outside of Nigeria (Abdullah et al, 2016;Akande et al, 2018;Maurelli et al, 2018;Shitta et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Fatemian et al (2018) reported 12 species of Ixodidae ticks from livestock fauna (sheep, goat, and cattle) in Boyer-Ahmad and Dena cities of Kohgiluyeh and Boyer-Ahmad Province, Southwest of Iran. Kebbi et al (2019) noted the infestation by 4 species of ticks in domestic dogs in Bejaia province, Northern Algeria. Also, the prevalence of infestation by ticks in young animals (≤ 1 year of age) was higher than that in adult animals (> 1 year of age).…”
Section: Resultsmentioning
confidence: 99%
“…This species is a three-host tick. In Algeria, it is present in the northern part of the country where it infests cattle, goats, dogs, wild boars and hedgehogs [ 8 , 37 , 42 , 49 , 50 ] Interestingly, we collected it from cats, which is a new host association for Algeria (Fig. 9 ).…”
Section: Discussionmentioning
confidence: 99%